Characteristics and clinical course of patients referred to the NST - Bong, Jeong Bin; Chung, Ji Yeon; Kim, So-Yeong; Ryu, Han Uk; Shin, Byoung-Soo; Kang, Hyun Goo (Frontiers in Nutrition, 2023)
Background and aims The nutrition support team (NST) comprises doctors, nutritionists, pharmacists, and nurses who provide intensive nutritional treatment designed for each patient by evaluating their nutritional status of hospitalized patients. This study aimed to identify the clinical characteristics of patients referred to the NST among those admitted to a tertiary hospital and to understand the factors affecting their clinical course and changes in pressure sore grades. Methods This study included 1,171 adult patients aged 18 years or older referred to the NST at a tertiary hospital in a metropolitan city between 1 January 2019 and 31 December 2020. Patients were divided into five age groups, neuro department and non-neuro department, those treated in the intensive care unit (ICU), and those not treated in the ICU. Patients were also compared based on the presence of pressure sores at the time of NST referral and changes in pressure sore grades at the first time of NST referral and discharge (improved pressure sores, no change in pressure sores, and aggravated pressure sores). In addition, this study examined the factors affecting changes in pressure sore grades. Results As age increased, the proportion of both low albumin levels and pressure sores significantly increased (p < 0.001), and the neuro department showed a significantly lower proportion of low albumin levels and pressure sores (p < 0.001). The proportion of patients with pressure sores was higher (64.9%), and this patient group showed significantly higher rates of low albumin levels (p < 0.001) and treatment in the ICU (p < 0.001). The group with aggravated pressure sore grades had a significantly higher proportion of patients in the surgery department (p = 0.009) and those treated in the ICU (p < 0.001). Admission to the surgery department was a factor that aggravated the grade of pressure sores [adjusted odds ratio (aOR) = 1.985, 95% confidence interval (CI) = 1.168–3.371]. When patients were not treated in the ICU, the grade of the pressure sores was less likely to worsen (aOR = 0.364, 95% CI = 0.217–0.609). Conclusion Pressure sores and low albumin levels are closely related, and the risk of developing and aggravating pressure sores is particularly high in patients in the surgery department and those receiving ICU treatment. Therefore, it is necessary to actively implement NST referral to ensure that overall nutrition, including albumin, is well supplied, especially for patients in the surgery department and treated in the ICU, as they are at high risk of pressure sore development and aggravation. Moreover, since low albumin levels frequently occur in elderly patients, it is necessary to consider including the elderly in the indications for referral to the NST.